Comparative effectiveness and acceptability of HIF prolyl-hydroxylase inhibitors versus for anemia patients with chronic kidney disease undergoing dialysis: a systematic review and network meta-analysis - Huang, Qiong; You, Minling; Huang, Weijuan; Chen, Jian; Zeng, Qinming; Jiang, Longfeng; Du, Xiuben; Liu, Xusheng; Hong, Ming; Wang, Jing (Frontiers in Pharmacology, 2023)
The comparative benefits and acceptability of HIF-PHIs for treating anemia have not been well researched to date. We sought to compare the effectiveness of 6 HIF-PHIs and 3 ESAs for the treatment of renal anemia patients undergoing dialysis. Data sources: Cochrane Central Register of Controlled Trials, PubMed, Embase, Cochrane Library, MEDLINE, Web of Science, and clinicaltrials.gov databases. Results: Twenty-five RCTs (involving 17,204 participants) were included. Regarding the efficacy in increasing Hb levels, roxadustat was more effective in improving Hb levels than vadadustat, recombinant human erythropoietin (rhEPO), and methoxy polyethylene glycol-epoetin beta (MPG-EPO), with mean differences (MDs) of 1.29 (95% CI: 1.08–1.55), 1.25 (1.13–1.38) and 1.36 (1.05–1.75), respectively. No significant differences were found between HIF-PHIs and ESAs in Hb response. Intervention with rhEPO showed a significantly higher risk of RBC transfusion than roxadustat, with an OR and 95% CI of 1.38 (1.07–1.78). Roxadustat and vadadustat had higher risks of increasing the discontinuation rate than ESAs; the former had ORs and 95% CIs of 1.58 (95% CI: 1.21–2.06) for rhEPO, 1.66 (1.16–2.38) for DPO (darbepoetin alfa), and 1.76 (1.70–4.49) for MPG-EPO, and the latter had ORs and 95% CIs of 1.71 (1.09–2.67) for rhEPO, 1.79 (1.29–2.49) for DPO, and 2.97 (1.62–5.46) for MPG-EPO. Conclusions: HIF-PHIs and ESAs have their characteristics and advantages in treating anemia undergoing dialysis. Compared with rhEPO, roxadustat appeared to be a potential treatment for DD-CKD patients due to its effectiveness in increasing Hb levels, decreasing the risk of RBC transfusion rate and regulating iron or lipid metabolism.